Factors Influencing E-Complaining: The Case of North Cyprus - Golestani, Mahnoosh (Eastern Mediterranean University EMU, 2017)
ÖZ: Şikayetçi davranış üzerine çalışmalar 1970’lerde başlamıştır. Şkayetçi davranış iş hayatındaki yönetim sürecinde yararlı olabileceği gibi memnuniyet ve memnun kalmama durumlarında ve şikayet yönetiminde etkin rol oynamaktadır. İnternet ve internetin getirdiği kolaylıklar müşterilere yaşadıkları tecrübelerini başka müşterilerle paylaşma şansı verir. Şikayetçi davranış ile ilgili belirlenen kararlar önemli bir görevdir ve şirketler için de önemli bir faktordür. Güncel çalışmalar özgüvenin e-şikayet üzerine etkilerini özel ve genel kavramsallaştırma olarak ele almayı denemektedir. Hatta, algılanan yararlılık ve algılanan kolay kullanım’ın e-şikayet üzerine etkileri araştırılacaktır. Bu konuda, bu araştırma: (i) genel özgüven’in müşteriler üzerine etkisinin e-şikayet ile bağdaşlaştırılması, (ii) özel özgüven’in müşteriler üzerine etkisinin e-şikayet ile bağdaşlaştırılması, (iii) alıgalanan kolay kullanımın e-şikayet üzerine olan etkisi, (iv) algılanan yararlılığın e-şikayet’ e olan etkisi konularını kapsamaktadır. Genel özgüvenin kavramsallaştırılması, kişisel özgüven, genel özgüven, algılanan kolay kullanım ve onların e-şikayet üzerine olan etkisi literatür incelemesi olarak anlatışmıştır. Bu amaca ulaşmak için, çalışma dört adet hipoteze dayandırılarak bahsi gecen faktörlerin e-şikayet’e olan muhtemel etkileri açıklanmıştır. T-test, ANOVA test ve verilerin regresyon analizi teknikleri kullanılarak dört hipotez oluşturuldu. Analiz sonuçlarına bakıldığında ise genel özgüven, özel özgüven, algılanan kolay kullanım konuları önemli derecede e-şikayet’in amacını etkilediğini, Diğer taraftan algılanan yararlılığın ise önemli derecede etkiye sahip olmadığı vi gözlemlenmiş ardından teorik ve yönetimsel bulguların etkileri, çalışmanın sınırlandırılması ve konu üzerine yapılabilecek ileriye dönük çalışmalar tartışılmıştır. Anahtar Kelimeler: Şikayetçi hareket, e-şikayet’in amacı, özgüven, genel özgüven, kişisel özgüven, algılanan kolay kullanım ve algılanan yararlılık.

The study of complaining behavior has started since 1970s. Complaining behavior is beneficial for business because it can manage the satisfaction and dissatisfaction situations and complaint administrating. Internet and its facilities give the customers an opportunity to share their experiences with other customers. Complaining behavior is a necessary factor for firms so determining factors which influence complaining behavior is an important task. Self-confidence is one of these factors. In the field of complaining behavior, self-confidence plays an important role. The present study tries to investigate the impact of self-confidence as general and specific conceptualizations on e-complaining. Also, the effects of perceived usefulness (PU) and perceived ease of use (PEOU) on e-complaining will be investigated. In that regards, this research has tried to establish whether: (i) general self-confidence has an impact on customer’s intention to e-complaining. (ii) Specific self-confidence has an impact on customer’s intention to e-complaining. (iii) Perceived ease of use has an effect on e-complaining and (iv) Perceived usefulness has an effect on ecomplaining. An expansive literature review was provided to conceptualize the general self-confidence, specific self-confidence, perceived ease of use and perceive usefulness. To achieve the goal, four hypotheses were considered to assess the possible impact of these factors on intention to e-complaining. T-test, ANOVA test and regression analysis of data were used to investigate the four hypotheses. The results indicated that general self-confidence, specific self-confidence and perceived ease of use had a significant effect on intention to e-complaining, whereas perceived usefulness was not significant. Following, the theoretical and managerial implication of findings, the limitation of the study and directions for next studies are discussed. Keywords: Complaining Behavior, Intention(s) to e-complaining, Self-confidence, General Self-confidence, Specific Self-confidence, Perceived ease of use and Perceived usefulness.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Assist. Prof. Dr. Emrah Öney
Keywords: Complaining Behavior; Intention(s) to e-complaining; Self-confidence; General Self-confidence; Specific Self-confidence; Perceived ease of use and Perceived usefulness; Customer Experiences-Customer Behavior; Business Administration; Marketing Management